Effect of low-cost irrigation methods on microbial contamination of lettuce irrigated with untreated wastewater - Keraita, Bernard N.; Konradsen, Flemming; Drechsel, Pay; Abaidoo, Robert C. (Wiley, 2007)
Objective  To assess the effectiveness of simple irrigation methods such as drip irrigation kits, furrow irrigation and use of watering cans in reducing contamination of lettuce irrigated with polluted water in urban farming in Ghana.Methods  Trials on drip kits, furrow irrigation and watering cans were conducted with urban vegetable farmers. Trials were arranged in a completely randomised block design with each plot having all three irrigation methods tested. This was conducted in both dry and wet seasons. Three hundred and ninety‐six lettuce, 72 soil, 15 poultry manure and 32 water samples were analysed for thermotolerant coliforms and helminth eggs.Results  Lettuce irrigated with drip kits had the lowest levels of contamination, with, on average, 4 log units per 100 g, fewer thermotolerant coliforms than that irrigated with watering cans. However, drip kits often got clogged, required lower crop densities and restricted other routine farm activities. Watering cans were the most popular method. Using watering cans with caps on outlets from a height <0.5 m reduced thermotolerant coliforms by 2.5 log units and helminthes by 2.3 eggs per 100 g of lettuce compared with using watering cans without caps from a height >1 m.Conclusion  Simple, cheap and easily adoptable irrigation methods have great potential to reduce crop contamination in low‐income areas. When used in combination with other on‐farm and post‐harvest risk reduction measures, these will help to comprehensively reduce public health risks from using polluted water in vegetable farming.